Phonon thermal conductivity limited by electron scattering in amorphous zr7oCU30. - Esquinazi, P.; de la Cruz, F. (American Chemical Society, 1983)
Fil: Esquinazi, P. Comisión Nacional de Energía Atómica; Argentina